Kenya : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
This progress report focuses on Medium-Term Plan (MTP) implementation by 2011 in Kenya, including specific progress on the attainment of MDG goals. The report presents the updated MTP program for 2012-13, including the consultations and framework underpinning its preparation. The macroeconomic framework and reformulation of the MTP Medium-Term Expenditure Framework is also discussed. It is concluded that significant progress has been made in meeting the MTP indicators and goals, although challenges remain in reducing poverty and meeting other MDGs.